A Look at Shahnon Ahmad's Revolusi yang Ditangguhkanfrom the Takmilah Perspective: (Revolusi Yang Ditangguhkan Karya Shahnon Ahmad Berdasarkan Perspektif Takmilah) (Malay Literature, 2016)
This study looks at Shahnon Ahmad's Revolusi Yang Ditangguhkan (2011) using the perspective of the Takmilah theory. The study aims to uncover the extent to which the writer, in this work, observes the seven principles of Takmilah outlined by Shafie Abu Bakar: (1) the principle of godliness as being kamal (perfect), (2) the principle of prophethood as a kamil (perfect) creation, (3) the principle that Islam is akmal (more perfect), (4) the principle of knowledge and literature as being takmilah (perfected), (5) the principle of literature itself as being aesthetic in nature as well as takmilah (perfect and perfecting), (6) the principle that the writer should continually practice istikmal (perfecting) of the self, and (7) the principle that readers should be encouraged to aim for becoming insan kamil (perfect beings). This study reveals the importance of the work–writer–audience relationship in conveying a message to society that is beneficial, for the betterment of the universal ummah.Keywords: Revolusi yang Ditangguhkan, Shahnon Ahmad, takmilah perspective